Relevance of intuition in language in a near native like performance of english as a second language - Romero Reyes,Cindy Xarelly; Zalazar Murcia, Pedro Antonio (San Salvador ; Universidad de El Salvador, 2005)
One of the questions that pops out in our minds once we have started learning a second language is: “Will I ever speak as well as native speaker does?” Teachers and students at the Foreign Language Department at the University of El Salvador may think it as an impossible goal. I am sure the reason of this failure is the emphasis we confer to grammar rules and consciously learned linguistic knowledge while we are performing in the second language. In contrast, native speakers performance, our aim to keep in mind, is based on Language Intuition. Intuition is the component of our minds, which directs the access to linguistic knowledge with no intermediate stages and “tells” the performer whether he is being accurate in his language production or not. They do not know this because of consciously learned knowledge of grammar rules. They just know it intuitively. Near native speakers may also develop such a sense for the target language in order to perform as well as a native speaker without the constant consultation of consciously learned grammar rules that take too much of time.
Tesis (Licenciatura en Idioma Inglés, Opción Enseñanza) --Universidad de El Salvador
Keywords: Inglés -- enseñanza; Métodos de enseñanza; Intuición (psicología)